Rapamycin Inhibits Cardiac Hypertrophy by Promoting Autophagy via the MEK/ERK/Beclin-1 Pathway - Gu, Jun; Hu, Wei; Song, Zhi-Ping; Chen, Yue-Guang; Zhang, Da-Dong; Wang, Chang-Qian (Frontiers in Physiology, 2016)
Rapamycin, also known as sirolimus, is an antifungal agent and immunosuppressant drug used to prevent organ rejection in transplantation. However, little is known about the role of rapamycin in cardiac hypertrophy and the signaling pathways involved. Here, the effect of rapamycin was examined using phenylephrine (PE) induced cardiomyocyte hypertrophy in vitro and in a rat model of aortic banding (AB) - induced hypertrophy in vivo. Inhibition of MEK/ERK signaling reversed the effect of rapamycin on the up-regulation of LC3-II, Beclin-1 and Noxa, and the down-regulation of Mcl-1 and p62. Silencing of Noxa or Beclin-1 suppressed rapamycin-induced autophagy, and co-immunoprecipitation experiments showed that Noxa abolishes the inhibitory effect of Mcl-1 on Beclin-1, promoting autophagy. In vivo experiments showed that rapamycin decreased AB-induced cardiac hypertrophy in a MEK/ERK dependent manner. Taken together, our results indicate that rapamycin attenuates cardiac hypertrophy by promoting autophagy through a mechanism involving the modulation of Noxa and Beclin-1 expression by the MEK/ERK signaling pathway.